Formulating purchasing strategies with kraljic portfolio matrix: A case study in an investment management company - Ulkhaq, M. Mujiya; Pratiwi, Trisna Nagris (Universitas Serang Raya, 2024)
Procurement is important in a company because it will directly affect how much a company can reduce costs. One of the activities in the procurement process is purchasing. PT XYZ has never conducted a supplier analysis or analysis of items purchased from suppliers. PT XYZ only purchases items daily; if managed properly, it can save the company's expenses and improve supplier relationships. This study aims to formulate purchasing strategies by implementing the Kraljic Portfolio Matrix (KPM). KPM has been widely applied to various cross-sectoral companies to manage suppliers more effectively. KPM divides items provided by suppliers into four quadrants based on supply risk and profit impact to minimize supply risk and maximize purchase profit. Thirty-five sup-pliers were analyzed in this study. The result shows that of the four KPM quadrants, three quadrants are filled, namely the non-critical quadrant (containing 12 suppliers), bottleneck (14), strategic (9), and none of the suppliers located in the leverage quadrant. Purchasing strategies based on these three quadrants are then formulated, and a total of seven strategies are produced. An analysis of the dominance of buyers and suppliers is also given to find out the relationship and balance of power between these parties.